Surveillance Strategy for Patients With BCLC Stage B Hepatocellular Carcinoma After Achieving Complete Remission: Data From the Real World - Wu, Ying; Shen, Lujun; Qi, Han; Cao, Fei; Chen, Shuanggang; Xie, Lin; Huang, Tao; Zhou, Danyang; Mo, Jinqing; Fan, Weijun (Frontiers in Oncology, 2020)
Purpose: There is a lack of consensus on the surveillance strategy for BCLC stage B hepatocellular carcinoma (HCC) patients with complete remission (CR). we performed a real-world, retrospectively analyzed the surveillance strategy for BCLC stage B HCC patients after radical therapy with CR to support clinical decision-making. Materials and Methods: We analyzed 546 BCLC stage B HCC patients with CR after radical treatments (surgery/ablation) at Sun Yat-sen University Cancer Center, from January 2007 to December 2019. Intensity of surveillance interval was defined as the mean of surveillance interval within 2 years. The primary endpoint of the study was overall survival (OS) and extra-Milan criteria relapse. Results: During a median follow-up time of 23.9 months (range 3.1-148.3 months), there were 11.9% of patients died, 56.6% of patients developed recurrence, the vast majority of patients experienced recurrence within 2 years, and 27.8% patients developed extra-Milan criteria recurrence. The median disease-free survival (DFS) and OS were 33.6 months and 60.0 months, respectively. Patients were divided into regular surveillance group (RS) (≤4.3 months) and irregular surveillance (IRS) group (>4.3 months) based on the optimal cutoff value of the intensity of surveillance interval. The RS group owned a lower incident of extra-Milan criteria relapse, smaller and fewer tumors at recurrence than IRS group which contributed to the prolonged OS. In addition, the cutoff values of surveillance interval that could lead to significant differences in the incidence of extra-Milan criteria relapse during 0-6, 6-12, and 12-18 months after CR were 2.6 months, 2.9 months, and 3 months, respectively. Conclusions: The average surveillance interval for patients with BCLC stage B HCC achieved CR should not exceed 4.3 months during the first 2 years’ follow-up. During three different phases of the initial 18 months after CR, individualized surveillance intervals that no more than 3 months were required to reduce the incidence of extra-Milan criteria relapse.